Determinants of domestic savings in Tanzania: Empirical evidence - Maureen Were; Cornel Joseph (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines trends and determinants of gross domestic savings in Tanzania using data for the period 1990-2020. The autoregressive distributed lag approach is employed to empirically analyse the short-run and long-run relationships. There has been a fairly stable increase in the domestic savings as a ratio of gross domestic product, though with considerable fluctuations over time. The empirical results show that in the long run, per capita income, public saving, and the ratio of broad money to gross domestic product as a proxy for financial deepening are significant determinants of private savings. On the other hand, terms of trade deter private savings. With regard to gross domestic savings, the results show that increases in per capita income, real deposit rate, and broad money positively influence savings, while inflation has a negative impact. Based on the results, we conclude that development policies geared towards increasing per capita incomes and financial deepening are fundamental in promoting domestic savings in Tanzania.
Keywords: E21; E29; E44; G51; 330; domestic savings; public saving; Tanzania